2011
DOI: 10.1016/j.fuproc.2010.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Air-steam gasification of sewage sludge in a bubbling bed reactor: Effect of alumina as a primary catalyst

Abstract: ARTICLE INFO ABSTRACT Keywords:Sewage sludge gasification Primary catalyst Bubbling fiuidised bed Gasifying agenteNumerous references can be found in scientific literature regarding biomass gasification. However, there are few works related to sludge gasification. A study of sewage sludge gasification process in a bubbling fiuidised bed gasifier on a laboratory scale is here reported. The aim was to find the optimum conditions for reducing the production of tars and gain more information on the influx of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 32 publications
6
51
0
1
Order By: Relevance
“…Anyway, compared with sludge tested by other authors [6, 9-11, 15, 18], it can be observed that values in Table 1 are in the same order. Although ashes content is lower [6,[9][10][11] or similar [22] to that of some sewage sludge already used for gasification experimentation, it is high compared with that of biomass normally used for gasification. Volatiles content is in the range of the values found in the literature for sewage sludge to be used as fuel for gasification [10,13,22] while different biomass-based fuels used for gasification in the literature may have higher [23][24][25] or lower [26] volatiles content.…”
Section: Fuel Propertiesmentioning
confidence: 90%
See 2 more Smart Citations
“…Anyway, compared with sludge tested by other authors [6, 9-11, 15, 18], it can be observed that values in Table 1 are in the same order. Although ashes content is lower [6,[9][10][11] or similar [22] to that of some sewage sludge already used for gasification experimentation, it is high compared with that of biomass normally used for gasification. Volatiles content is in the range of the values found in the literature for sewage sludge to be used as fuel for gasification [10,13,22] while different biomass-based fuels used for gasification in the literature may have higher [23][24][25] or lower [26] volatiles content.…”
Section: Fuel Propertiesmentioning
confidence: 90%
“…A main advantage of sewage sludge gasification is that a high-quality flammable gas may be obtained, so it can be directly used for electricity generation or for supporting the drying of sewage sludge [5] and also may be employed as raw material in chemical synthesis processes [6]. Indeed, as for biomass gasification, a main difficulty about sewage sludge gasification is the presence of tar and dust in the synthesis gas produced, which may cause problems in process equipment and/or in turbines and engines for gas distribution [7][8][9][10][11]. In any case, gasification is considered a waste-to-clean energy technology [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found no published studies that reported kinetic data on individual reactions from biosolids gasification, but did find three experimental studies that reported on laboratoryscale sewage sludge bubbling fluidized-bed gasifiers (de Andrés, 2011;Kang et al, 2011;Manyà, 2006). The proximate and ultimate analyses of the sewage sludges used and the syngas produced in those studies are listed in Tables 5 and 6, respectively.…”
Section: Model Calibrationmentioning
confidence: 99%
“…Following calibration of the model using the 18 data sets from literature (de Andrés et al, 2011;Kang et al, 2011;Manyà et al, 2006), the remaining 10 data sets from the same three experimental studies were used as independent data for final model performance validation, as seen in Figure 5. Using these data, statistical analysis was performed using the Ansari-Bradley method to compare the predicted gaseous compositions with the literature values.…”
Section: Model Validationmentioning
confidence: 99%